2009
DOI: 10.1080/09593330802573795
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on and mechanism of simultaneous removal of Hg0, SO2 and NO from flus gas using NaClO2 solution

Abstract: Experiments on the simultaneous removal of mercury (Hg0), sulphur dioxide (SO2) and nitric oxide (NO) from flue gas using sodium chlorite solution (NaClO2) were carried out in a bench-scale bubbling reactor. The effect of initial pH on Hg0 removal efficiency was investigated. The results show that the efficiency of Hg0 removal was higher in acid condition. The effect of the concentrations of SO2 and NO from simulated flue gas on Hg0 removal efficiency with NaClO2 solution was examined. The Hg0 removal efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The outlet Hg 0 concentration decreases to about 0 μg/m 3 in the first 0.5 h, and after 0.5 h, the Hg 0 removal activity shows a slow increase. In fact, Hg 0 can react with NaClO 2 according to eq . , With further increases of the NaClO 2 concentration to 5 mM, the efficient Hg 0 removal duration of NaClO 2 increases to 1 h. This result indicates that, with the increase of NaClO 2 concentration, there is enough NaClO 2 in the limestone slurry to react with Hg 0 , thus significantly enhancing the Hg 0 removal activity. However, an unexpected phenomenon appears with the increase of the NaClO 2 concentration.…”
Section: Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The outlet Hg 0 concentration decreases to about 0 μg/m 3 in the first 0.5 h, and after 0.5 h, the Hg 0 removal activity shows a slow increase. In fact, Hg 0 can react with NaClO 2 according to eq . , With further increases of the NaClO 2 concentration to 5 mM, the efficient Hg 0 removal duration of NaClO 2 increases to 1 h. This result indicates that, with the increase of NaClO 2 concentration, there is enough NaClO 2 in the limestone slurry to react with Hg 0 , thus significantly enhancing the Hg 0 removal activity. However, an unexpected phenomenon appears with the increase of the NaClO 2 concentration.…”
Section: Results and Discussionmentioning
confidence: 93%
“…Moreover, NO and SO 2 could promote the Hg 0 oxidation activity, thus improving the mercury removal activity in limestone slurry. Zhao et al , explored the performance of NaClO 2 for simultaneous removal of Hg 0 , NO, and SO 2 in a bench-scale bubbling reactor. It was found that Hg 0 could be easily removed under acidic conditions, and 72.91% Hg 0 removal efficiency could be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that NaClO 2 was converted to ClO 2 by UV irradiation under mild alkaline condition. The ClO 2 yield ascended from 1.6 × 10 –6 to 1.9 × 10 –4 mol/L with UV irradiation time varying from 0 to 600 s. As the redox potential of ClO 2 /Cl – (1.511 V) was higher than that of ClO 2 – /Cl – (0.76 V), this strong oxidant contributed to the oxidation absorption of NO from simulated flue gas through eq . It was worth noting that when UV irradiation time reached 300 s, the enhancement factors of NO and NO x increased up to 2.0 and 1.5, respectively. These results implied that removal efficiencies of NO and NO x by NaClO 2 solution were significantly improved by UV pretreatment.…”
Section: Resultsmentioning
confidence: 98%
“…The oxidative power for these active species is in the order of HClO 2 > ClO 2 ≫ ClO 2 − . 37 Normally, the fractional compositions of active chlorine species in NaClO 2 solution vary largely with solution pH. With the decrease of solution pH from 8.0 to 2.4, more NaClO 2 in solution will exist in forms of HClO 2 and ClO 2 .…”
Section: Methodsmentioning
confidence: 99%